Penggunaan Permainan Kartu Domino Untuk Meningkatkan Kemampuan Hafalan Mufrodat Bahasa Arab Pada Siswa Kelas VII Di MTs Tarbiyatus Shibyan Surabaya - Moh. Faizin; M. Dzikrul Hakim Al-Ghozali; Machnunah Ani Zulfah (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2020)
Abstract Vocabulary is an element of Arabic that must be absorbed by language learners to acquire communication skills in these languages. Therefore understanding vocabulary is very important for understanding Arabic and without understanding vocabulary, students cannot understand Arabic well. Therefore, researchers used a domino card game to improve the ability to memorize mufrodat. This research aims to determine the effectiveness of the using of domino cards to improve the ability to mufdorat memorizing in seventh grade at the tsanawiyah surabaya madrasah . This research uses Quasi Experiment in the form of Nonequivalent Control Group Design. Data collection is generated by observation, interview, testing and documentation . The results of the experimental design conducted by researchers showed that learning using domino cards is effective. This is proven by the value of sig. (2-tailed) of the post-test in the control and experimental class is smaller than sig. 0.05 which is 0,000. The conclusion from these results is :